Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a = 1/(1.2) + 5/(2.3) + ... + 89/(9.10)
a = [1-1/(1.2)] + [1-1/(2.3)] + ... + [1-1/(9.10)]
\(a=\left(1-\frac{1}{1.2}\right)+\left(1-\frac{1}{2.3}\right)+...+\left(1-\frac{1}{9.10}\right)\)
\(a=9-\left[\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{9.10}\right]\)
Ta có:
\(\frac{1}{1.2}=\frac{1}{1}-\frac{1}{2}\)
\(\frac{1}{2.3}=\frac{1}{2}-\frac{1}{3}\)
....
\(\frac{1}{9.10}=\frac{1}{9}-\frac{1}{10}\)
Cộng các vế ở trên lại:
\(\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{9.10}=\frac{1}{1}-\frac{1}{10}=\frac{9}{10}\)
Vậy:
a = 9 - 9/10 = 81/10
a) \(\frac{-2}{3}\)- 3x = 0,75 + 5x
3x + 5x = \(\frac{-2}{3}\)- 0,75
8x = \(\frac{-17}{12}\)
x = \(\frac{-17}{12}\): 8
x =\(\frac{-17}{96}\)
Vậy x = \(\frac{-17}{96}\)
b) \(\frac{11}{12}\)- (\(\frac{2}{5}\)+ x ) = \(\frac{2}{3}\)
\(\frac{2}{5}\)+ x = \(\frac{11}{12}\)-\(\frac{2}{3}\)
\(\frac{2}{5}\)+ x = \(\frac{1}{4}\)
x = \(\frac{1}{4}\)- \(\frac{2}{5}\)
x = \(\frac{-3}{20}\)
Vậy x = \(\frac{-3}{20}\)